The challenge of multiple sclerosis: How do we cure a chronic heterogeneous disease? - Weiner, Howard L. (Annals of neurology, 2009)
Multiple sclerosis is (MS) a T‐cell autoimmune disease characterized by a relapsing‐remitting followed by a progressive phase. Relapses are driven by the adaptive immune system and involve waves of T helper cell 1 (Th1), Th17, and CD8 cells that infiltrate the nervous system and provoke a attack. These cells are modulated by regulatory T and B cells. Infiltration of T cells into the nervous system initiates a complex immunological cascade consisting of epitope spreading, which triggers new attacks, and activation of the innate immune system (microglia, dendritic cells, astrocytes, B cells), which leads to chronic inflammation. The secondary progressive phase is due to neurodegeneration triggered by inflammation and is driven by the innate immune system. Why a shift to the progressive stage occurs and how to prevent it is a central question in MS. Effective treatment of MS must affect multiple disease pathways: suppression of proinflammatory T cells, induction of regulatory T cells, altering traffic of cells into the nervous system, protecting axons and myelin, and controlling innate immune responses. Without biomarkers, the clinical and pathological heterogeneity of MS makes treatment difficult. Treatment is further hampered by untoward adverse effects caused by immune suppression. Nonetheless, major progress has been made in the understanding and treatment of MS. There are three definitions of cure as it applies to MS: (1) halt progression of disease, (2) reverse neurological deficits, and (3) prevent MS. Although the pathways to each of these cures are linked, each requires a unique strategy. Ann Neurol 2009;65:239–248